CAPITAL STRUCTURE AND FINANCIAL STABILITY AT NON-FERROUS METTALURGY ENTERPRISES IN KAZAKHSTAN - Kokeyeva, Samal; Abylaikhanova, Tana; Niyazbekova, Shakizada (Scientific Journal of Pedagogy and Economics, 2021)
the company’s financing sufficiency and sustainability are achieved through the effective use of borrowed and own funds, which guarantees companies’ solvency and creditworthiness. In Kazakhstan, many companies do not adhere to theoretical methods for optimizing the capital structure, leading to an unstable financial state. In most cases, the financing policy, long-term development, does not correspond to its strategic goals. Failure to create directions for the capital structure formation at each development stage and improper use of borrowed funds leads to a limitation of the development pace and non-fulfilment of strategic directions. It leads to non-compliance with the owners’ interests. The capital structure optimization plays a crucial role in making decisions on activities and financing investment projects. Although scientists from different countries have widely studied this topic, this topic still requires an in-depth study on the example of developing countries. Since most scientific papers are written only at the organizational level, the impact of leverage on various industries has yet to be studied. The paper aims to analyze the determinants and tools for creating capital structure in the metallurgical industry. It will allow us to determine ways to improve its financial stability. By identifying the factors that affect the capital structure, we can identify the factors that affect the company’s overall sustainability. This will allow us to study the capital structure patterns in developing countries and help determine ways to improve its financial stability.